2018
DOI: 10.1098/rsif.2018.0492
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics of elastic lamellae: unravelling the role of structural inhomogeneity in multi-scale arterial mechanics

Abstract: Microstructural deformation of elastic lamellae plays important roles in maintaining arterial tissue homeostasis and regulating vascular smooth muscle cell fate. Our study unravels the underlying microstructural origin that enables elastic lamellar layers to evenly distribute the stresses through the arterial wall caused by intraluminal distending pressure, a fundamental requirement for tissue and cellular function. A new experimental approach was developed to quantify the spatial organization and unfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 60 publications
1
44
1
Order By: Relevance
“…We observed that lamellar layers unfold in the pressure range between 0 and 30 mm Hg. This is in line with earlier findings of Yu et al [21] and with those of Dobrin, who used radiography to measure the deformation of four elastic lamellae in the dog carotid artery and found complete lamellar unfolding at a pressure between 25 and 55 mm Hg [50]. We also found that lamellar layers stretch (i.e.…”
Section: Unfolding Stretching and Thinning Of Lamellar Layers With Psupporting
confidence: 93%
See 2 more Smart Citations
“…We observed that lamellar layers unfold in the pressure range between 0 and 30 mm Hg. This is in line with earlier findings of Yu et al [21] and with those of Dobrin, who used radiography to measure the deformation of four elastic lamellae in the dog carotid artery and found complete lamellar unfolding at a pressure between 25 and 55 mm Hg [50]. We also found that lamellar layers stretch (i.e.…”
Section: Unfolding Stretching and Thinning Of Lamellar Layers With Psupporting
confidence: 93%
“…This observation contradicts previous histology-based findings, which suggested that lamellae are only stretched once the intraluminal pressure surpasses the diastolic pressure [51]. It is, however, in line with the observations of Yu et al, who reported that unfolding and extension of lamellar layers contribute simultaneously to tissue-level deformation [21]. Another observation that is consistent with the findings of Yu et al is that the outer interlamellar layer (L23) is slightly thicker than the inner interlamellar layer (L12).…”
Section: Unfolding Stretching and Thinning Of Lamellar Layers With Pcontrasting
confidence: 63%
See 1 more Smart Citation
“…The cut ring "opens" to minimize stored strainenergy, as the inner wall is in compression and the outer wall in tension (Humphrey 2002). This residual stress is the result of differences in the waviness of the elastic lamellae between the inner and outer wall (Yu et al 2018a). Direct quantification of residual stress (Λ) is not a simple task.…”
Section: Residual Stressmentioning
confidence: 99%
“…To optimize the mechanical function, knowledge in the mechanisms of microstructural deformations and local strains at different loading conditions is important (Disney et al 2018). Fiber sliding, deformation, uncrimping, and alignment are some mechanisms which are investigated in inflation and tensile measurements, combined with optical methods (Yu et al 2018). Measurements on microstructural organization using multiphoton microscopy are also used to establish constitutive models of local mechanical environment within biological tissues and to investigate the relationship between biological responses and mechanical stimuli (Wan et al 2012).…”
Section: Nano/micromechanics Testingmentioning
confidence: 99%